2022
DOI: 10.1152/ajplung.00146.2022
|View full text |Cite
|
Sign up to set email alerts
|

Cellular senescence is increased in airway smooth muscle cells of elderly persons with asthma

Abstract: Senescent cells can drive age-related tissue dysfunction partially via a senescence-associated secretory phenotype (SASP) involving pro-inflammatory and pro-fibrotic factors. Cellular senescence has been associated with a structural and functional decline during normal lung aging and age-related diseases such as chronic obstructive pulmonary disease (COPD) and idiopathic pulmonary fibrosis (IPF). Asthma in the elderly (AIE) represents a major healthcare burden. AIE is associated with bronchial airway hyperresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 96 publications
0
9
1
Order By: Relevance
“…While asthma commonly affects conducting airways, airway dysfunction in elderly asthmatics is more likely to also involve peripheral airways [ 58 ]. Using impulse oscillometry (IOS), a forced oscillation technique that more accurately distinguishes the origin of lung resistance between large airways and small airways, a recent study showed that elderly asthmatics had significantly higher resistance in both large and small airways than younger asthmatics [ 59 ]. Similar findings are observed in middle-aged 9-month-old mice, who had greater airway inflammation and AHR in response to acute house dust mite challenge than younger 3-month-old mice [ 60 ].…”
Section: Asthma In the Elderly Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…While asthma commonly affects conducting airways, airway dysfunction in elderly asthmatics is more likely to also involve peripheral airways [ 58 ]. Using impulse oscillometry (IOS), a forced oscillation technique that more accurately distinguishes the origin of lung resistance between large airways and small airways, a recent study showed that elderly asthmatics had significantly higher resistance in both large and small airways than younger asthmatics [ 59 ]. Similar findings are observed in middle-aged 9-month-old mice, who had greater airway inflammation and AHR in response to acute house dust mite challenge than younger 3-month-old mice [ 60 ].…”
Section: Asthma In the Elderly Pathogenesismentioning
confidence: 99%
“…Similar findings are observed in middle-aged 9-month-old mice, who had greater airway inflammation and AHR in response to acute house dust mite challenge than younger 3-month-old mice [ 60 ]. In regard to airway thickening and remodeling, airway wall thickness is found to be decreased with age [ 61 , 62 ]; however, elderly asthmatics were observed to have thicker airway walls compared to nonelderly asthmatics [ 59 ]. Additionally, elderly asthmatics have higher sputum levels of pentosidine, a collagen cross-linker, than younger asthmatics [ 63 ].…”
Section: Asthma In the Elderly Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Asthma in elderly is generally characterized by an increase in sputum neutrophils, lower airway caliber variability, and air trapping 156 . Lung tissues from elderly asthmatics have an increased expression of multiple senescent markers such as phospho‐p53 and p21, and they show greater airway fibrosis compared with age‐matched elderly persons without asthma and young age controls 157 . In patients with stable and oral corticosteroid (OCS)‐independent asthma, urinary metabotype is characterized by reduced carnitine expression and in those with severe asthma by the carnitine transporter SLC22A5 158 .…”
Section: Clinical Data Altered Metabolism In Senescence: Focus On Ast...mentioning
confidence: 99%
“…Upon aging, pulmonary function reduction and residual volume increase are observed, with a more evident decline in pulmonary function in patients suffering from asthma ( 6 ). Aghahi et al reported greater airway fibrosis in older individuals with asthma compared with control groups consisting of young and older individuals ( 7 ). However, thickening of the smooth muscles of airways is not related to the duration of asthma ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%